Smart Flood Preparedness: Mitigation and Preparedness Education - Mihrawaty S. Antu; Wahyuni Umar; Tania Aurelia Hiola; Annisa Baili; Sulmina; Yulisti H. Igirisa; Ulfa Idris; Andini Putri Hasan (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Abstract: Floods are natural disasters that consistently dominate disaster events in Indonesia and have a significant impact on economic, social, environmental, health, and educational aspects. Data from the National Disaster Management Agency (BNPB) shows that floods cause damage to infrastructure, loss of assets, disruption of economic activities, and an increased risk of post-disaster illness and fatalities. Gorontalo Province is an area with a high level of flood vulnerability, especially Gorontalo City. Based on Gorontalo Provincial Statistics data in 2024, there were 9 sub-districts affected by floods, 47 out of 50 villages submerged, and as many as 39,784 people affected. This flood condition not only has an impact on the residential environment, but also threatens public facilities such as schools. Standing water in the school environment has the potential to damage educational infrastructure and increase the risk of diseases such as diarrhea, acute respiratory infections (ARI), leptospirosis, and skin diseases. Therefore, the involvement of schools in flood disaster mitigation efforts is very important. Schools have a strategic role as a center for disaster education and behavior change through increased knowledge, preparedness, and disaster mitigation simulations. Integrated disaster education in the school environment is expected to be able to increase the preparedness of school residents and effectively reduce the impact of floods.